2021
DOI: 10.3390/su13042210
|View full text |Cite
|
Sign up to set email alerts
|

Standardization of the Dimensions of a Portable Weighing Lysimeter Designed to Be Applied to Vegetable Crops in Mediterranean Climates

Abstract: The progress made in developing information and communication technologies (ICTs) and the fact that water resources are becoming increasingly scarce make precision agriculture a very valuable tool for efficient and sustainable crop management, particularly for irrigation and fertilisation. In line with this, the water balance estimate is considered one of the most accurate methods for estimating crops’ water requirements. The Agromotic Engineering and Sea Research Group of the Universidad Politécnica de Cartag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 23 publications
0
9
0
1
Order By: Relevance
“…It indicated that the contribution percentage of annual average precipitation to X. italicum distribution is not high, but it still has a certain impact on X. italicum growth. A possible explanation is that the regions with a temperate maritime climate, Mediterranean climate, and temperate continental monsoon climate are relatively humid, and the temperature of humid air is more stable than that of dry air 59 . Therefore, the annual mean temperature does not decrease significantly in the above-mentioned areas, so did not cause a change in the suitable area of X. italicum .…”
Section: Discussionmentioning
confidence: 99%
“…It indicated that the contribution percentage of annual average precipitation to X. italicum distribution is not high, but it still has a certain impact on X. italicum growth. A possible explanation is that the regions with a temperate maritime climate, Mediterranean climate, and temperate continental monsoon climate are relatively humid, and the temperature of humid air is more stable than that of dry air 59 . Therefore, the annual mean temperature does not decrease significantly in the above-mentioned areas, so did not cause a change in the suitable area of X. italicum .…”
Section: Discussionmentioning
confidence: 99%
“…The DT was placed beneath the CT and behind an intermediate control tank, quantified by means of one load cell (15 kg) with a resolution of 0.03 mm (3 g). The effectiveness for the quantification of the input/output water volumes to the soil in the CT was validated in a previous study [4].…”
Section: Test Preparationmentioning
confidence: 95%
“…In fruit crops different irrigation management strategies can be employed, e.g., partial root-zone drying or regulated deficit irrigation. However, in horticultural crops, these strategies are not feasible when water is scarce as it was summarized in a recent review [3] where other strategies are proposed mainly based on the use Information and Communication Technologies (ICTs) for efficiently managing water resources [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in 2018, aiming to monitor the ET c of a vegetable crop such as potato, the same mini-L prototype with identical technical characteristics [27], but with different dimensions (1.5 × 0.69 × 0.5 m), was installed close to the LWL (see Figure 1). The cultivation tank containing the reconstructed soil has a surface area of 1.04 m 2 and a total weight of around 0.9 Mg.…”
Section: Study Site Description and Lysimeter Data Processingmentioning
confidence: 99%